Diagnostic Testing for Degenerative Disc Disease. (12th July 2012) - Hasz, Michael W.
Abstract : The diagnostic of degenerative disc disease should be reached with the help of various diagnostic studies. This article briefly review the information gained by the following tests: radiographs, computed tomography, magnetic resonance, and discography. The article explains how each modality provides a piece of the diagnostic puzzle and how discography confirms the origin of the patient's pain.